Repertório ocupacional de crianças de 4 a 6 anos com atraso no desenvolvimento motor, da linguagem e na habilidade pessoal-social - Tima, Fredcarme (2020)
Child development is understood through the acquisition and improvement of various skills that will enable children to perform the typical occupations and activities of this life cycle. If the children have difficulties in acquiring skills corresponding to the age group they are in, it is considering as a developmental delay. Children with developmental delay may have limitations and / or difficulties in achieving these occupations and activities depending on the area (s) with impairment. Being a difficult diagnosis to establish, these children are often categorized as idle among others and do not always receive the help they need to learn how to develop their age skills. For this reason, the objective was to evaluate the occupational repertoire of children from 4 to 6 years old with delayed development of motor coordination, language and personal-social ability. This is a descriptive cross-sectional study with a quantitative approach. The sample consisted of 17 children from 4 to 6 years old regularly enrolled in a Municipal Center of Early Childhood Education in the city of São Carlos, interior of São Paulo, indicated by the teachers for presenting difficulties in performing school tasks. These children were assessed by the Denver II Screening Test for detecting delay or suspected developmental delay and the Paediatric Activity Card Sort (PACS) for checking activity patterns of children categorized into four occupational dimensions - personal care, sports, school / productivity and hobbies and social activities. With the results of the Denver II Screening Test, the development of 10 children was classified as "suspect", as they scored two or more items with "caution" and one item with "delay" and 7 children as "abnormal", one since they scored two or more with “delay”. The gross motor area is the most affected in both groups. On the other hand, the occupational repertoire of children with delay and suspected delay shows many similarities in relation to the activities they perform and the categories in which they perform the most.